Pelaksanaan Penyuluhan Dalam Mencegah Tindak Pidana Kekerasan Seksual Terhadap Anak - Eunike Sabrina Damanik (Indonesian Journal of Police Studies, 2020)
From 2016 to 2019 there was a drastic increase in the case of child sexual abuse which is dangerous and threatens the safety of the child, damages personal and can cause delays in children's development, and disrupts the sense of comfort, peace, and security of children. Sat Binmas which has duties and responsibilities in the preemptive and preventive fields plays an important role in efforts to prevent the occurrence of criminal acts of sexual violence against children. In this study, the aim is to analyze and describe the implementation and the factors that influence the implementation of counseling in preventing sexual violence against children. This study uses qualitative research methods with field research techniques. Using data triangulation with 4 techniques namely sources, theories, and techniques as well as primary data sources and secondary data. Data validity is data reduction, data display, conclusion drawing, and verification. This research uses role theory, communication theory, and SWOT analysis as well as the concept of implementing counseling and counseling activities and the concept of sexual violence on children. In the implementation of binluh, the value is less than optimal analyzed from the target/target in receiving binluh, then the media used are still considered inappropriate or less desirable by school students so that the expected effects/impacts of binluh are considered less than optimal. The conclusion is the influencing factors in the performance by sat binmas is the lack of competence of members, methods of education, and determination of binluh targets.